The Mobilization, Speciation and Transformation of Organic and Inorganic Contaminants in Soil-Groundwater Ecosystems (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue explores research on soil and groundwater management and environmental sustainability. Thirteen articles highlight methodologies and technologies to address pollutant dynamics, groundwater protection and urban planning. The Special Issue aims to provide practical solutions and foster collaboration among professionals dedicated to environmental sustainability and resilience.